Importance of Internationalization of Small and Medium-Sized Enterprises and Family Businesses in the Development of Tourism in Slovakia - Kašťáková, Elena; Jarossová, Malgorzata A. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2023)
Currently, the topic of the importance of the internationalization of small- and medium-sized enterprises (SMEs) and family businesses is getting stronger and is immediately becoming more relevant also in the use of tourism. It is widely discussed not only at the state level, but also at international forums. The aim of this contribution is to examine the importance of internationalization of SMEs and the formation of family businesses (also with a focus on women in business) for the development of tourism on the example of Slovakia. SMEs in the Slovak Republic in the field of tourism face many challenges in the field of internationalization and export support, whether in financing, education, cooperation with academic institutions. It is necessary to focus on support in the field of education of SMEs, the family business and women in business, the creation of a unified database of Slovak exporters for tourism, support the creation of specialized associations of foreign trade of SMEs in the field of tourism, financing of export activities of SMEs in the tourism industry and the creation of specialized associations of foreign trade of SMEs with a focus on tourism.
Kašťáková, E. i Jarossová, M. A. (2023). Importance of Internationalization of Small and Medium-Sized Enterprises and Family Businesses in the Development of Tourism in Slovakia. W: T. Lesiów (red.), Doskonalenie jakości usług przewodnickich w dobie pandemii (s. 154-164). Wrocław: Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu.
Keywords: internationalization; family business; small and medium-sized enterprises; Slovakia; tourism; internacjonalizacja; biznes rodzinny; małe i średnie przedsiębiorstwa; Słowacja; turystyka